2017
DOI: 10.1080/17453674.2017.1344915
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate use of arthroscopic meniscal surgery in degenerative knee disease

Abstract: Background and purposeCurrent evidence suggests that arthroscopic knee surgery has no added benefit compared with non-surgical management in degenerative meniscal disease. Yet in many countries, arthroscopic partial meniscectomy (APM) remains among the most frequently performed surgeries. This study quantifies and characterizes the dynamics of the current use of knee arthroscopies in Switzerland in a distinctively non-traumatic patient group.MethodsWe assessed a non-accident insurance plan of a major Swiss hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 34 publications
5
17
1
9
Order By: Relevance
“…As previously observed in another Swiss study analysing inappropriate use of arthroscopic meniscal surgery in degenerative knee disease, 41 a substantial amount of the patients in our sample underwent CA as inpatients in contrast to other healthcare settings. This finding is most likely explained by differences in the organisation of the healthcare system in Switzerland.…”
Section: Discussionsupporting
confidence: 52%
“…As previously observed in another Swiss study analysing inappropriate use of arthroscopic meniscal surgery in degenerative knee disease, 41 a substantial amount of the patients in our sample underwent CA as inpatients in contrast to other healthcare settings. This finding is most likely explained by differences in the organisation of the healthcare system in Switzerland.…”
Section: Discussionsupporting
confidence: 52%
“…A Swiss study of patients aged >40 years reported a 9% reduction in knee arthroscopy rates, from 388 to 352 per 100 000 between 2012 and 2015, with no described administrative or political regulations. 20 Finland, Denmark and Sweden have publicly accessible databases which all use the Nomesco classification and include privately financed procedures (sampo.thl.fi, sundhedsstyrelsen.dk and socialstyrelsen.se, respectively). From 2012 to 2016, arthroscopy rates per 100 000 in Sweden decreased from 206 to 157 (24%), in Denmark from 290 to 183 (37%) and in Finland from 339 to 187 (52%).…”
Section: Discussionmentioning
confidence: 99%
“… 4 22 Financial incentives are likely to influence surgical rates, especially in the private sector. 20 23 …”
Section: Discussionmentioning
confidence: 99%
“…Our investigation showed that knee arthroscopy (all procedures and low-value procedures) decreased between 2010 and 2014. A recent study using Swiss health insurance claims also showed a decrease in surgical volume between 2012 and 2015, although the authors also found patients’ type of insurance coverage was associated with undergoing a knee arthroscopy 27. Comparisons between insurance types (particularly public vs privately insured patients) in Australia and low-value procedures have yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%